The Impact of ESG Scores on Corporate Financial Performance: Moderating Role of Gender Diversity - Setiani, Eko Putri (Nominal: Barometer Riset Akuntansi dan Manajemen, 2023)
ABSTRACTThis study aims to examine the impact of environmental, social and governance (ESG) scores on corporate financial performance and the moderating role of gender diversity in this relationship. This study uses 80 samples of companies listed on the Indonesian stock exchange. Samples were taken using a purposive sampling approach. The dependent variable in this study is corporate financial performance, the independent variable is the ESG scores, the moderating variable is gender diversity.  In the context of this study, a high ESG score describes a company that has a high risk in ESG. The hypothesis was tested using multiple regression analysis. The results of this research show that there is a negative relationship between ESG risk scores and corporate financial performance. The empirical analysis provides evidence for a moderating effect of gender diversity on the relationship between ESG scores and corporate financial performance.  Investors need to pay attention not only to financial aspects but also to environmental, social and governance aspects as non-financial factors in making investment decisions.Keywords: ESG Scores, Financial Performance, Gender DiversityABSTRAKPenelitian ini bertujuan untuk menguji dampak skor environmental, social dan governance (ESG) terhadap kinerja keuangan perusahaan. Penelitian ini menggunakan 80 sampel perusahaan yang terdaftar di bursa efek Indonesia. Sampel diambil menggunakan pendekatan purposive sampling. Variabel dependen dalam penelitian ini adalah kinerja keuangan perusahaan, variabel independen adalah skor ESG, variabel pemoderasi adalah keragaman gender. Dalam konteks penelitian ini, skor ESG yang tinggi menggambarkan perusahaan yang mempunyai risiko ESG tinggi. Hipotesis penelitian diuji menggunakan analisis regresi berganda. Hasil penelitian menunjukkan adanya hubungan yang negatif antara skor risiko ESG dan kinerja keuangan perusahaan. Analisis empiris memberikan bukti adanya efek pemoderasi dari keragaman gender terhadap hubungan antara skor ESG dengan kinerja keuangan perusahaan. Investor tidak hanya perlu untuk memperhatikan aspek keuangan saja tetapi juga perlu memperhatikan aspek lingkungan, sosial dan tata kelola sebagai faktor non keuangan dalam pengambilan keputusan investasi.Kata Kunci: ESG Skor, Kinerja Keuangan, Keragaman Gender, Tata Kelola